Perlindungan Hukum Bagi Perusahaan Debitur Pailit dalam Menghadapi Pandemi Covid 19 - Ronald Saija; Kadek Agus Sudiarawan (Fakultas Hukum Universitas Pattimura, 2021)
The emergence of the Covid-19 pandemic on global economic development has an impact not only on the world economy and investment, but also correlates with aspects of legal development, especially business economy law. One of the areas of business economy law that has also undergone changes in an effort to accommodate the development of modern business transaction practices is bankruptcy law. The purpose of this research is to examine the preventive efforts made by Debtors at Bankrupt Companies to reduce bankruptcy caused by Covid-19 and solutions to protect debtors in companies experiencing bankruptcy. The research method used is juridical normative, primary and secondary legal materials with a statutory approach and a conceptual approach. The results showed that the regulations regarding bankruptcy law in various countries, including Indonesia, tended to change. For example in Europe, in the last few decades European countries have argued that the existing insolvency legal framework has not been able to provide a better economic legal scheme compared to liquidation schemes, so that changes in the substance of bankruptcy have occurred in almost all aspects of the country including the Union. Europe, the American continent, the Asian continent, the African continent, and the Australian continent.